Report on professional attachment with ABB Support Pte Ltd - Tai, Tony Seow Woi (2009)
This report is to provide details and information on the professional attachment in ABB Support Pte Ltd. It also provides feedback and suggestion to the attached organisation as well as to the Office of Professional Attachment (OPA). This will allow improvement to be made for future attachment.